Ser-se outro Legalizado: Práticas de Falsificação de Documentos na Clandestinidade Comunista - Nogueira, Cristina (Trabalhos de Antropologia e Etnologia, 2020)
This article analyses the communist clandestinity, as a form of resistance to the dictatorship established in Portugal and overthrown with the 25 April Revolution. Going underground meant that a performance had to be adopted in order to allow the “clandestine” to survive and escape the police raids. This article aims to describe this process and to debate the issue of identity and the way the clandestine militants saw themselves. This article is understood as a part of an important ongoing debate.